Main landmarks in the history of European law (XI–XVIII centuries) - Pylypchuk, O. O. (History of science and technology, 2018)
The article is devoted to the history of the development of European law in the Middle Ages and the Enlightenment. The process of Roman law codification in continental Europe has been examined. The contribution of glogators and consiliators in the process of developing systems of legal science and knowledge in the territories of foreign countries has been shown. The development of legal science and education in the era of Enlightenmen has been given. In particular the activities of monarchs-philosophers, the introduction of the principles of natural law into European law as well as the process on development of European criminal law have been shown. The principles on formation of the Anglo-Saxon legal system have been highlighted. The history on the development of the state and the right of the Russian Empire, which, in the nineteenth century, belonged most part of the Ukrainian lands has been explained. The contribution of European and Russian law to the development of Ukrainian legal science in the second half of the nineteenth century has been revealed.